Infl uence of Drinking Water Supplementation With Licorice Extract on Certain Blood Traits of Broiler Chickens During Heat Stress - Al – Daraji, Hazim. J. (Pharmacognosy Communications)
Background: This study was conducted to examine the physiological mechanisms involved in alleviating the detrimental effects of heat stress on broiler chickens by supplementing drinking water with licorice extract (LE). Methods: A total of 600 one day old broiler chicks were used. Birds have been assigned to 4 treatment groups with 3 replicates of 50 chicks each (150 chicks per treatment). Birds in the fi rst treatment (T1) were provided drinking water alone and considered as a control group. Birds in treatments 2 (T2), 3 (T3) and 4 (T4) were provided drinking water supplemented with 150, 300 or 450 mg LE/liter, respectively. Hematological traits included in this study were: Erythrocyte counts (RBC), hemoglobin concentration (Hb), thrombocyte counts (Thr), leucocyte counts (WBC), heterophil/lymphocyte ratio (H/L ratio), hematocrit (pcv) and plasma levels ofuric acid (Uri), glucose (Glu), cholesterol (Cho), Protein (Pro), aspartate aminotransaminase activity (AST), alkaline phosphatase activity (ALP), calcium (Cal) and phosphorus (Pho). Results: It was found that inclusion of LE in the drinking water of broiler chickens exposed to heat stress resulted in signifi cant (p < 0.05) increases in RBC, Hb, Thr, WBC, PCV, and plasma Uri, Glu, AST, ALP, Ca and Pho and signifi cant (p < 0.05) decreases in H/L ratio, and plasma Cho and Pro compared with T1. T4 recorded the best results with relation to all blood characteristics included in this experiment. Conclusions: It was concluded from this study that supplementation of LE (particularly at the level of 450 mg/liter) to the drinking water of broiler chickens can depress the adverse effects of heat stress on general physiological status.